Agri-environmental schemes in the European Union - Kissné Nagy, Csilla (Acta Agraria Debreceniensis, 2014)
Some details on agri-environmental measures in EU have been presented in this paper. Territorial, financial and regulation-specific aspects have been investigated based on statistics from EUROSTAT and ENFRD reports. It has been concluded, that AES shows a much diversified picture in the EU. For example, by 2009 the old members and new member states of EU had different proportions of agricultural area (25% and 10%, respectively), where AES had been introduced. Differences in AES are remarkable both at the level of member states as well as in the amounts of payments per hectare. The reasons behind this are the different national conditions and approaches on AES as well as differences in time these measures had been introduced in member countries. The final conclusion is that further increases may be expected in the coming years regarding the area involved in different agri-environmental measures and the total amount of AES payments in the EU.